ADAPTATION OF RELIGIOUS MODERATION: Dispersion of Wasathiyah Islam as the Treasure of PTKIN in Aceh - M. Anzaikhan; Syamsul Bahri; Sufrizal Sufrizal (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
Indonesia is a unitary state that adheres to a democratic system even though most of its population is Muslim. Radical Islamic circles use this reality to shake the sovereignty of elected leaders. As a result, the concept of religion and state ideology often clash through the rise of hoaxes and hate speech. In response, religious moderation is the Ministry of Religion's mainstay program to educate the public so that they are not easily exposed to radical views. The program's seriousness is embedded in various policy rhythms regarding outreach, education, ASN selection, seminars, and research grants at Perguruan Tinggi Keagamaan Islam Negeri (PTKIN). Under the Ministry of Religion, PTKIN Aceh should follow up on the religious moderation program the Government echoes. In fact, not all Aceh PTKIN academics accept religious moderation in totality, program deviations often occur, where PTKIN claims to be moderate before the Ministry of Religion but is anti-moderation when involved in society. This article belongs to field research with a qualitative approach. The methodology used is a descriptive analysis study with a comparative format for various PTKINs in Aceh. The research locations were IAIN Langsa, IAIN Lhokseumawe, UIN-Ar-Raniry, STAIN Dirundeng Meulaboh, and IAIN Takengon. The research findings conclude that the different forms of implementation of religious moderation between the Government and PTKIN Aceh are due to adaptation and dispersion (deviations). The dispersion of religious moderation in PTKIN in Aceh is influenced by scientific adaptation, leadership authority adaptation, local wisdom adaptation, and political adaptation.